Optimisation of the sorption capacity of sulphuric acid activated IBUSA clay in palm oil bleaching using response surface methodology. (1st January 2014) - Ofochebe, Sunday M.; Ozoegwu, Chigbogu G.
In this paper, response surface methodology is applied for a detailed optimisation study of the sorption capacity of commercial adsorbent in physical bleaching of palm oil. The study utilised a partial distillation process implemented on a vacuum bleacher using locally sourced IBUSA clay activated with sulphuric acid as the adsorbent medium. The performance of the fractional factorial array in predicting the bleaching capacity of the adsorbent and the interactive sorption effects of the system variables which include; acid concentration, reaction temperature, contact time, adsorbent dosage and particle size distribution are tested within the response surface optimisation algorithm. The result predicts optimum adsorption efficiency of 70.74% at sulphuric acid concentration, reaction temperature, contact time, adsorbent dosage and particle size values of 5.57 mol/l, 122.44°C, 51.73 minutes, 1.78 wt.%, and 347.32 μm respectively. The adequacies of the predictive model and the proposed optimisation method at large are tested using standard statistical criteria and experimental validation.